Mania. Issue 3 (June 2015) - Dubovsky, Steven L.
Abstract : Purpose of Review: : Primary mania and hypomania in full or subsyndromal forms are the defining features of bipolar disorder and are common in neurologic patients, as are manic syndromes precipitated by medications used to treat neurologic disorders. This article addresses the diagnosis, pathophysiology, treatment, and course of bipolar disorder after a manic episode as well as mania as a manifestation of neurologic disease. Recent Findings: : Mania can be a primary psychiatric disorder but can also be a symptom of a neurologic disorder, especially right-sided cerebrovascular disease. Treatments (such as corticosteroids and dopaminergic agents) for neurologic illnesses regularly induce mania. The neurobiology of primary mania and bipolar disorder involves alterations in intracellular signaling, changes in gene expression, neural network interactions, and apoptosis. Except when induced by time-limited treatment with a provoking agent, mania tends to be highly recurrent and to alternate or be exhibited alongside depression. Symptoms of mania become more complex and treatment refractory with time, although effective treatment improves the long-term outcome. Summary: : Behavioral manifestations of mania may be more obvious than affective symptoms, especially in patients with aprosodia. Atypical antipsychotic drugs are often first-line acute treatments, but the evidence supporting their long-term prophylactic efficacy is questionable. In addition to being an established mood stabilizer, lithium has putative neuroprotective properties, although a side effect can be impaired memory.